O. P. Ergenbright (Editor), Revised Ordinances of the City of Independence, Kansas, Together with the Amended Laws Governing Cities of the Second Class and Standing Rules of the City Council 162, § 27 (1887) - (:unkn) unknown (General Publisher, 1887)
Prohibited using a pistol or other weapon in a hostile or threatening manner. Also prohibited carrying a concealed pistol, dirk, Bowie knife, revolver, slungshot, billy, brass, lead, or iron knuckles, or any deadly weapon. Punishable by fine of $5-100.
--
Keywords: BRANDISHING; CARRY - CONCEALED